The Christmas that changed everything / Faye Acheampong. - Acheampong, Faye (Harlequin Enterprises ULC, 2023)
Toy shop manager Naomi is determined to make this Christmas a record breaker. But when The Entertainment Emporium's Santa falls ill, Naomi needs a stand-in--quick! And buttoned-up accountant Will is her only option... As they're forced to spend the festive season together in heart-racing proximity, Naomi starts to see the real Will. But revealing her true self could change everything... Dare she let Will unwrap her guarded heart?